The Analysis of Servant Leadership and Individual Characteristics on Employee Performance through Knowledge Sharing at Badan Kesatuan Bangsa Dan Politik (Bakesbangpol) Kabupaten Sidoarjo - Sukarno, Gendut; Akhfan, Evan Saka (Formosa Journal of Multidisciplinary Research, 2024)
This aim of this study is to evaluate the impact of servant leadership and individual characteristics on employee performance at the Badan Kesatuan Bangsa dan Politik Kabupaten Sidoarjo, with knowledge sharing as a mediating variable. Data were collected through questionnaires from 31 employees using saturated sampling technique. The analysis was conducted using the Partial Least Square (PLS) method. The results show that servant leadership and individual characteristics contribute directly to employee performance. However, when mediated by knowledge sharing, the two variables did not show a significant contribution to performance. The findings provide insight into the relationship between the four variables in the context of these government agencies.